Factor XIIIA subunit and Crohn's disease. Issue 1 (January 1993) - Hudson, M; Wakefield, A J; Hutton, R A; Sankey, E A; Dhillon, A P; More, L; Sim, R; Pounder, R E
Abstract : Factor XIIIA is the active subunit of plasma factor XIII that is responsible for cross linking fibrin into a stable clot. Sixteen patients with Crohn's disease were studied prospectively from relapse (Crohn's disease activity index > 150) into remission. Plasma factor XIIIA concentrations were significantly lower in active disease (median 63 (95% CI 46-72) U/dl) than remission (median 90 (95% CI 60-112) U/dl; p = 0.002). Plasma factor XIIIA concentrations correlated positively with the activity index (p = 0.005) and platelet count (p = 0.003), and negatively with serum albumin (p = 0.006). In five patients with persistent aggressive disease, the factor XIIIA concentration remained below the lower range of normal despite apparent clinical improvement in response to medical treatment. Tissues from three patients who underwent surgical resection during the study were immunostained for factor XIIIA. Gut mucosal and submucosal macrophages stained strongly for factor XIIIA. In one patient, capillary thrombi near superficial mucosal erosions immunostained for factor XIIIA in macroscopically normal mucosa. Similar changes were identified in more severely inflamed sections of intestine from the other two patients. The demonstration of significantly low plasma factor XIIIA concentrations in active Crohn's disease, and the immunostaining of factor XIIIA in capillary thrombi in the bowel wall, suggest that activation of coagulation may be involved in the pathogenesis of Crohn's disease. The plasma factor XIIIA concentration may prove a useful laboratory marker of disease activity.